Estudo de driver para acionamento de lâmpada LED aplicado em iluminação pública - Fachinello, Lucas Alberto (2015)
The street lights came up in order to provide comfort and safety but for the population in the absence of sunlight, however it is evident the need of researching new, more efficient lighting that current used. The English LED technology (Lighting Emitting Diode) has emerged as an option for street lighting because according Camponogara (p.41 2012) are more resistant to shock, vibration, have long service life and are more efficient when compared to vapor lamps sodium used in street lighting. This paper presents a comparison of the topologies of converters DC-DC non-isolated applied to LED luminaires drive for street lighting. It will present the design and simulation of buck topologies, buck-boost, Cuk, SEPIC and ZETA for two load configurations, the first named Project 1 consists of an array of 40 LEDs power connected in series, with a total power of 75W and the second (Project 2) for two vectors parallel of 20 LEDs each, also totaling 75W. After the project and the simulation will be discussed the efforts that each topology exercises in its semiconductors, size of engineered components and topologies can maintain a maximum level of 1% variation of voltage and current in the load. Subsequently a comparison between the two projects will be done by determining which of the projects exerts less effort in semiconductors. The topology chosen represented the PC stage (power controller) the switching operation of the LEDs.